Effect of antipsychotics on breast tumors by analysis of the Japanese Adverse Drug Event Report database and cell-based experiments - Tae Maeshima; Ryosuke Iijima; Machiko Watanabe; Satoru Yui; Fumio Itagaki (BMC, 2021)
Abstract Background Since antipsychotics induce hyperprolactinemia via the dopamine D2 receptor, long-term administration may be a risk factor for developing breast tumors, including breast cancer. On the other hand, some antipsychotic drugs have been reported to suppress the growth of breast cancer cells in vitro. Thus, it is not clear whether the use of antipsychotics actually increases the risk of developing or exacerbating breast tumors. The purpose of this study was to clarify the effects of antipsychotic drugs on the onset and progression of breast tumors by analyzing an adverse event spontaneous reporting database and evaluating the proliferation ability of breast cancer cells. Methods Japanese Adverse Drug Event Report database (JADER) reports from April 2004 to April 2019 were obtained from the Pharmaceuticals and Medical Devices Agency (PMDA) website. Reports of females only were analyzed. Adverse events included in the analysis were hyperprolactinemia and 60 breast tumor-related preferred terms. The reporting odds ratio (ROR), proportional reporting ratio (PRR), and information component (IC) were used to detect signals. Furthermore, MCF-7 cells were treated with haloperidol, risperidone, paliperidone, sulpiride, olanzapine and blonanserin, and cell proliferation was evaluated by WST-8 assay. Results In the JADER analysis, the IC signals of hyperprolactinemia were detected with sulpiride (IC, 3.73; 95% CI: 1.81-5.65), risperidone (IC, 3.69; 95% CI: 1.71-5.61), and paliperidone (IC, 4.54; 95% CI: 2.96-6.12). However, the IC signal of breast tumors was not observed with any antipsychotics. In cell-based experiments, MCF-7 cells were treated with six antipsychotics at concentrations of 2 and 32 μM, and none of the drugs showed any growth-promoting effects on MCF-7 cells. On the other hand, blonanserin markedly suppressed the growth of MCF-7 cells at a concentration of 32 μM, and the effect was concentration dependent. Conclusions Analysis of the JADER using the IC did not show breast tumor signals due to antipsychotic drugs. In in vitro experiments, antipsychotics did not promote MCF-7 cell proliferation whereas blonanserin suppressed MCF-7 cell growth. Further research on the effects of blonanserin on the onset and progression of breast tumor is expected.